2019
DOI: 10.1002/ijc.32799
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker profile for prediction of response to SMAC mimetic monotherapy in pediatric precursor B‐cell acute lymphoblastic leukemia

Abstract: Second mitochondria‐derived activator of caspase (SMAC) mimetics (SMs) targeting inhibitor of apoptosis proteins (IAPs) activate cell death pathways, and are currently being evaluated in clinical trials. Their successful therapeutic implementation requires upfront identification of patients who could benefit from a SM‐based treatment but biomarkers for SM sensitivity have not yet been described. Here, we analyzed the intrinsic activity of two monovalent (AT406 and LCL161) and two bivalent (Birinapant and BV6) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 45 publications
(142 reference statements)
0
9
0
Order By: Relevance
“…In a recent study, Zinngrebe et al reported the identification of gene expression markers that could help in stratifying patients that were particularly sensitive to SMs. This was done in B-cell acute lymphoblastic leukemia (BCP-ALL) and found four commonly predictive genes, which were TSPAN7, DIPK1C, MTX2 and TNFRSF1A, the latter encoding TNFR1 (Zinngrebe, et al, 2020).…”
Section: Biomarkers For Treatment Response To Smac Mimeticsmentioning
confidence: 99%
“…In a recent study, Zinngrebe et al reported the identification of gene expression markers that could help in stratifying patients that were particularly sensitive to SMs. This was done in B-cell acute lymphoblastic leukemia (BCP-ALL) and found four commonly predictive genes, which were TSPAN7, DIPK1C, MTX2 and TNFRSF1A, the latter encoding TNFR1 (Zinngrebe, et al, 2020).…”
Section: Biomarkers For Treatment Response To Smac Mimeticsmentioning
confidence: 99%
“…One of the main challenges is to identify and develop biomarkers of response to birinapant. Several studies have assessed and demonstrated that IAP levels do not correlate with sensitivity to birinapant ( 48 , 49 ). Zinngrebe et al demonstrated that protein expression levels of cIAP1 and XIAP were similar in SMAC mimetic-sensitive and SMAC mimetic-insensitive primary B-cell acute lymphoblastic leukemia samples ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have assessed and demonstrated that IAP levels do not correlate with sensitivity to birinapant ( 48 , 49 ). Zinngrebe et al demonstrated that protein expression levels of cIAP1 and XIAP were similar in SMAC mimetic-sensitive and SMAC mimetic-insensitive primary B-cell acute lymphoblastic leukemia samples ( 48 ). McCann et al also reported that expression of IAP proteins alone could not be correlated to birinapant sensitivity in a panel of colorectal cancer cell lines ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 Therapeutic targeting of members of the IAP superfamily was investigated in patients with advanced solid tumors 16,17 and hematologic malignancies. [18][19][20][21][22][23][24][25] Infante et al were the first to investigate the oral, monovalent, SMAC mimetic LCL161, in a first-in-human, large phase 1, dose-escalation clinical trial in patients with advanced solid tumors, demonstrating overall safety and feasibility of administering this once-weekly, oral medication. Furthermore, upon correlative study in this clinical trial, LCL161 showed downmodulation of cellular IAP1 (cIAP1), demonstrating, as hypothesized, an on-target effect of this novel agent.…”
Section: Strikingly Survival Outcomesmentioning
confidence: 99%